Fuel Saving and CO2 Emission Reduction Analysis During Single Engine Taxi-Out Implementation to Airbus A320 at Soekarno Hatta Airport in Jakarta - Ade Julizar; Muhamad Jayadi (Jurnal Teknologi Kedirgantaraan, 2026)
The aviation industry faces increasing pressure to improve operational efficiency and reduce carbon emissions. This study investigates the potential fuel savings and CO₂ emission reductions resulting from the implementation of Single Engine Taxi-Out (SETO) procedures for Airbus A320 aircraft operating at Soekarno-Hatta International Airport (CGK), Jakarta. Using flight operational data and taxi-out duration observations via FlightRadar24, fuel savings were estimated by comparing conventional dual-engine taxi operations to SETO procedures. Results show that adopting SETO for all A320 departures at CGK could yield annual fuel savings of approximately 8,870,960 kg, equivalent to 28,032,233 kg of CO₂ reduction. These findings demonstrate that SETO offers substantial environmental and economic benefits while aligning with ICAO’s net-zero emission targets. However, successful implementation depends on rigorous safety assessments, proper crew training, and regulatory approval.